'Social media, gender, and the mediatisation of war': a reply to Shim and Stengel. Issue 2 (3rd July 2017) - Shepherd,
Abstract : This is a reply to:Shim, David and Stengel, Frank A. 2017. "Social media, gender and the mediatization of war: exploring the German armed forces' visual representation of the Afghanistan operation on Facebook." Global Discourse . 7 (2–3): 330–347. https://doi.org/10.1080/23269995.2017.1337982